2013
DOI: 10.1016/j.arr.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Food for thought: The role of appetitive peptides in age-related cognitive decline

Abstract: Through their well described actions in the hypothalamus, appetitive peptides such as insulin, orexin and leptin are recognized as important regulators of food intake, body weight and body composition. Beyond these metabolic activities, these peptides also are critically involved in a wide variety of activities ranging from modulation of immune and neuroendocrine function to addictive behaviors and reproduction. The neurological activities of insulin, orexin and leptin also include facilitation of hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 222 publications
2
46
0
2
Order By: Relevance
“…Directly connecting the effects of a HF diet on energy metabolism to its effects on cognition is a large body of evidence suggesting that the insulin receptor is highly expressed in the hippocampus and cortex, that synaptic insulin signaling is critical for learning and memory, and that peripheral insulin insensitivity can have dramatic effects in the CNS [98104]. Consistent with insulin’s potential role in learning and memory, a number of the studies reviewed here have found that HF diet-related cognitive impairment is also associated with impaired peripheral and central insulin signaling [16,19,20,22,23, 76].…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Directly connecting the effects of a HF diet on energy metabolism to its effects on cognition is a large body of evidence suggesting that the insulin receptor is highly expressed in the hippocampus and cortex, that synaptic insulin signaling is critical for learning and memory, and that peripheral insulin insensitivity can have dramatic effects in the CNS [98104]. Consistent with insulin’s potential role in learning and memory, a number of the studies reviewed here have found that HF diet-related cognitive impairment is also associated with impaired peripheral and central insulin signaling [16,19,20,22,23, 76].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…It is also now well established that the leptin receptor is highly expressed in several brain regions including the hippocampus [105, 106] and recent evidence suggests that leptin signaling, like insulin, may have a critical role in hippocampal dependent learning through regulation of synaptic plasticity and trafficking of neurotransmitter receptors [104,107109]. While several studies have found that leptin resistance is associated with cognitive deficits [3,110,111], and that administration of leptin into the hippocampus enhances LTP [112] while also modulating food-related learning [113], leptin levels do not appear to have been routinely measured in most studies of HF diet-related cognitive impairment.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Diabetes has recently been implicated as a risk factor for several neurological diseases, including Alzheimer's and Parkinson's disease (Luchsinger et al, 2001; Hu et al, 2007; Jolivalt et al, 2008, 2010, 2012; Fadel et al, 2013). This has led to increased interest in the role that insulin might play in the nervous system and it is becoming very clear that there is a strong link between diabetes and Alzheimer's disease (Ribe and Lovestone, 2016).…”
Section: Insulin and The Nervous Systemmentioning
confidence: 99%
“…Due to the extensive terminal field, central orexin signaling is well positioned to integrate and orchestrate multiple physiological processes such as arousal, whole-body energy metabolism, reward seeking, autonomic function, and ventilatory control (Burdakov et al, 2013; de Lecea and Huerta, 2014; Karnani and Burdakov, 2011; Kotz et al, 2012; Mahler et al, 2012). Aberrant orexin function has been associated with several pathophysiologies, such as obesity, narcolepsy and other sleep disorders, as well as the occurrence and severity of age-related disorders (Fadel et al, 2013). Here we briefly review the literature documenting the role of orexin in sleep disorders, energy balance, and aging.…”
Section: Introductionmentioning
confidence: 99%